PEMROSESAN DATA UTANG PIUTANG DENGAN MENERAPKAN SISTEM INFORMASI AKUNTANSI BERBASIS WEB: (STUDI KASUS PT.ZBEEF INDONESIA) - Budi Safta Nugraha; Didik Kurniawan (Jurnal Pepadun, 2021)
PT. Zaky Beef (Zbeef Indonesia) is a company engaged in General Services and Trading, namely as a Beef Cattle Supplier in the Bandar Lampung Region, which is located at Jl. Pisang Tanduk No. 51 Sub-District of Susunan Baru, Tanjung Karang Barat District, Bandar Lampung City. Apart from providing beef cattle to its customers, namely distributors and small shops. The Accounting Information System in Depts Process is a computerized and web-based accounting information system that is useful for recording the process of accounts payable in business activities. It is necessary to record accounts payable so that business owners can make the right decisions in managing their business. The Accounting Information System Depts Process has been developed by providing several features to facilitate the recording of the accounts depts process. These features are Login, Feedlot, Customer, Cattle Data, Purchases, Cattle Stock, Sales, Company Accounts Payable Data, Customer Receivable Data, Account Data, Reports. The development of this system uses the PHP programming language and uses the waterfall method, while for modeling software using STARUML and MariaDB as data storage media with a database management system by MySQL. The system testing technique used in this research is blackbox testing for testing its functionality, while non-functional testing is done by giving a questionnaire. The test results obtained are in good category and in accordance with user requirements but still need to be developed to maximize features.